P10.12 Role of condyloma acuminata in incident hiv infection: a population-based cohort study in taiwan 2000–2010. (13th September 2015) - Zou, H; Chen, Y; Strong, C; Li, C; Ko, W; Ko, N
Abstract : Introduction: The role of Condyloma Acuminata (CA) in incident HIV infection has not been well documented. We aimed to elucidate this relationship by analysing a large national cohort. Methods: Medical claim records 2000–2010 of 1 million individuals randomly selected from the Taiwan National Health Insurance Research Database (NHIRD, approximately 23 million individuals in total) were retrieved. We included all patients treated for CA (PWCs) and patients screened for and confirmed without CA (PWOCs). We matched five patients never screened for CA (PNCs) for every one PWC by year of first CA treatment/first clinical visit, gender and age. PWCs, PWOCs and PNCs were followed from the date of first CA treatment, first CA screening and first clinical visit, retrospectively. Endpoint was incident HIV infection. Chi-square test was used to compare socio-demographic characteristics among patients. Characteristics with a P value of <0.1 using univariate Cox regression were entered into a multivariate Cox regression model to calculate adjusted hazard ratio (aHR) of incident HIV infection. Results: We included 1539 PWCs, 1106 PWOCs and 7695 PNCs. The three groups were comparable with respect to age, gender, location and income. HIV incidence was 284.0 (95% confidence interval (CI): 164.9–489.1), 110.6 (95% CI: 41.5–294.7) and 3.8 (95% CI: 0.5–27.2) per 100, 000 person-years among PWCs, PWOCs and PNCs, respectively. Compared to PNCs, PWCs were 66.4 (8.6–510.2) times and PWOCs 33.7 (3.8–303.5) times more likely to have incident HIV infection. Other variables associated with incident HIV infection were being a male (aHR = 10.5, 95% CI: 2.4–46.1), being under 30 years of age (aHR = 3.5, 95% CI: 1.9–9.5) and syphilis diagnosis with treatment before HIV infection (aHR = 4.5, 95% CI: 1.0–19.7). Conclusion: CA is associated with elevated incident HIV infection. HIV risk reduction interventions among patients with CA are warranted. Disclosure of interest statement: This study is funded by the Taiwan Ministry of Science (Project ID: 1030087343). All authors declare no conflict of interest.